THE CONTRIBUTION OF CENTRAL ASIAN SCIENTISTS TO THE DEVELOPMENT OF SCIENCE DURING THE ABBASIAN PERIOD - Sevinch Sukhratovna Tilabjonova (European Science Publishing, 2024)
This article highlights the significant contribution of the scholars of our country to the renaissance of Islam. It is also reported that the Abbasid caliphs created wide opportunities for the development of science and constantly supported the people of science. It should also be recognized that the city of Baghdad is highly developed as a center of science. It is also noteworthy that all necessary conditions were created for young people who are hungry for knowledge from different parts of the Caliphate to gather knowledge in a single center.
Keywords: Abbasids, Mowarounnahr, Khurasan, Damascus, Baghdad, Harun al-Rashid, Al-Ma'mun, Musa al-Khorazmi, Ahmad al-Farghani, Abu Nasr Farabi.